How background affects design output: Teaching product development to mechanical engineers, industrial designers and managers - Silva, A.; Silva, J. V.-B. da.; Leite, M.; Simões, R. (2016 2nd International Conference of the Portuguese Society for Engineering Education (CISPEE), 2016)
Product design and development is a topic of academic and industrial research, with particular current interest. Emphasis on innovation and entrepreneurship, design thinking and creativity have been recently pulled together into the teaching and research on product design and development. However, the shear breadth of the topic means that there is no single way of teaching and doing research on it. The present paper looks into the similarities and differences across three very similar product development masters courses at three distinct Portuguese higher education institutions — Instituto Superior Tecnico (IST) of the University of Lisbon, Instituto Politecnico do Cavado e Ave (IPCA), and ISCTE business school (IBS) of Instituto Universitario de Lisboa. Product Development and Entrepreneurship is taught at IST mostly for students of mechanical engineering, whereas Advanced Product Development Methodologies is taught at IPCA mostly for industrial design students and New Product Development is taught at ISCTE for business students. All three courses use the same methodology of assessment and the same overall syllabus, with distributed assignments and expected outcomes. However, the nature and emphasis of specific aspects of the students' projects are fundamentally different. The reasons for these differences are analyzed by the faculty involved, in the context of the students' background and goals and examples are given. Conclusions and recommendations are provided at the end.